School Choice In Kazakhstan: Parental Strategies And Policy Drivers - Sakhimbekov, Birzhan; Tleuov, Askat (BUKETOV BUSINESS REVIEW, 2025)
In Kazakhstan, schools in areas with fast population growth operate in multiple shifts to accommodate growing student populations amid limited infrastructure capacity. This challenge requires public policy initiatives in enrollment forecasting and school construction. In developing forecasting models, it is important to understand parental choices in school selection. Drawing on 24 in-depth interviews, this study investigates how parents navigate school choice among those from varied socioeconomic and geographic backgrounds. The research identifies nine key factors influencing decision-making, including perceptions of school quality, safety, accessibility, reputation, language of instruction, and cultural alignment. Framed through Bourdieu’s theory of capital and Gewirtz et al.'s concept of schooling circuits, the analysis reveals that parental choices reflect both long-term aspirations and immediate structural constraints. These choices, while often strategic and informed, are shaped by systemic inequities, such as disparities in infrastructure, access to inclusive education, and digital resources, that affect educational opportunities across social groups. The study shows how parental agency both reproduces and resists prevailing inequalities. The findings provide valuable insights for policymakers aiming to align education infrastructure and planning with the needs of families in transitional contexts.